Effects of Group Narrative Therapy on Feeling of Inferiority and Attachment Styles in Married Women Experienced Marital Infidelity - Habibeh Ghaffari; Farzaneh Mikaeli Manee; Shahed Masoudi (Gonabad University of Medical Sciences, 2022)
Background: Marital infidelity damages marriage and increases the tensions between couples. The present study aims to evaluate the effect of group narrative therapy on feeling of inferiority and attachment styles in married women experienced marital infidelity. Methods: This is a quasi-experimental study with a pretest/posttest design using a control group. The study population consists of all women experienced marital infidelity referred to Peidayesh Counseling Center in Mashhad, Iran. Of these, 40 eligible women were selected using a convenience sampling method and assigned into intervention (n=20) and control (n=20) groups. Data collection tools were Hazan and Shaver (1986)'s Adult Attachment Questionnaire and Eysenck (1988)'s Inferiority Questionnaire. Group narrative therapy was performed in the intervention group at 7 sessions while the control group did not receive any intervention. Data analysis was performed by univariate and multivariate analysis of covariance in SPSS software, v. 22. Results: Group narrative therapy had significant effects on feeling of inferiority and all three secure, avoidant and ambivalent attachment styles (P=0.001). Conclusion: Group narrative therapy can reduce feelings of inferiority and avoidant and ambivalent attachments and increase secure attachment in women experienced marital infidelity. This method can be used to improve psychological problems of these women.